Pluralism and Justice in Islamic Inheritance Law: Contextualization and Harmonization of Sharia Principles with Indonesian Social Realities - Muhammad Hafis; Juliani Syafitri; Jumni Nelli (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2026)
This study aims to uncover the historical-philosophical foundations of pluralism in Islamic inheritance law through the Prophet Muhammad's mechanism of accommodation towards pre-Islamic traditions ('urf), as well as to provide an integrative methodological framework for contextualizing inheritance justice. This study is significant because it addresses the limitations of previous studies, which were descriptive and partial, by exploring the dynamic roots of Sharia in responding to socio-historical realities. This study employs an integrative qualitative approach with three analytical frameworks: first, philosophical-historical: tracing the dialectic between universal values (tsawābit) and contextual values (mutaghayyirāt) in inheritance law through asbāb al-nuzūl and pre-Islamic Arab social realities. Second, thematic-holistic: connecting inheritance verses (QS. An-Nisā’: 11-12) with the principle of justice across texts (QS. Al-Ḥujurāt: 13, Al-Mā’idah: 8) and maqāṣid al-syari’ah (hifẓ al-māl, al-nafs, al-nasl). Third, empirical-contextual: testing the implementation of universal-particular values in the Indonesian context. Based on this study, it can be concluded that the 2:1 inheritance ratio is responsive-contextual to the pre-Islamic Arab social structure (financial responsibility of men), not a rigid rule. The principle of universal justice in the Qur’an (‘adl, maṣlaḥah) opens space for recontextualization in the modern era, such as the Minangkabau hybrid model or the 1:1 share allocation that considers women’s economic contributions. This integrative framework of text-maqāṣid-contextuality offers a new perspective in inheritance ijtihad, promoting flexibility in Sharia based on substantive justice without disregarding the authenticity of the text. Policy implications include strengthening consultation mechanisms in the Compilation of Islamic Law (Article 183) and progressive reinterpretation in religious courts.